Geomorphology and faulted zones: an approach on some selected areas of Greece using GIS. A multi-criteria inference mechanism. - Gournelos, Th.; Sabot, V.; Evelpidou, N.; Vassilopoulos, A.; Skianis, G. (8th PanHellenic Geographical Conference, 2007)
In this paper we investigate the relations between the landforms and the discontinuous tectonism. A multistep methodology has been adopted. Thus, first we study the topography of a given area and by proper procedures we classify the geoforms. We next examine the geological formations of the area, the drainage system, the landuse, the vegetation and the human impact. Finally, we study the tectonic zones of this area (faults and fractures zones). Data has also been obtained by airphotos and satellite images. All the above information is analyzed in a G.I.S platform using expert system methodology. This procedure has been applied to some selected places of the Greek territory.